The value of blood examination in the diagnosis of disease - Caldwell, Fred Wallace (My University, 1907)
Introduction: Physiologically the blood may be considered simply as a medium of exchange, collecting the tissue forming elements from the lungs and the assimilated products of the digestion of the food, distributing these to the various tissues of the body there to be made use of in the anabolic changes, and in turn collecting the products of catabolism to carry these to the liver and the excretory organs -- skin, kidneys, lungs and possibly the bowels. Histologically it may be considered as a tissue composed of colorless blood cells and red blood cells, floating in a liquid, the blood plasma. The colorless cells originate in lymphoid tissue and in bone marrow. There are several varieties of colorless cells recognized, which includes the following: 1. Small lymphocytes, about the same size as the red cell and containing a relatively large nucleus. This variety probably originates wholly within lymphoid tissue. 2. Large mononuclear leucocytes, three times as large as the red cells and containing a nucleus. 3. Transitional leucocytes representing a more advanced stage of development, and containing a nucleus often kidney shaped or indented. 4. Polynucleur leucocytes. This is the form found most abundand and represents the fully developed leucocyte. This variety is recognized by the distorted nucleus…
Citation: Caldwell, Fred Wallace. The value of blood examination in the diagnosis of disease. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Blood; Disease Diagnosis; Composition of Blood; Theses